2009
DOI: 10.1016/j.jsb.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid flip-flop modulated by transmembrane peptides WALP and melittin

Abstract: Select transmembrane proteins found in biogenic membranes are known to facilitate rapid bidirectional flip-flop of lipids between the membrane leaflets, while others have no little or no effect. The particular characteristics which determine the extent to which a protein will facilitate flip-flop are still unknown. To determine if the relative polarity of the transmembrane protein segment influences its capacity for facilitation of flip-flop, we have studied lipid flip-flop dynamics for bilayers containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 69 publications
(158 reference statements)
1
56
0
Order By: Relevance
“…It is worth noting in this context, that a number of experimental studies have concluded that antimicrobial peptide adsorption can induce more rapid lipid flip-flop rates in the bilayers. Fattal et al 47 and Matsuzaki et al 48 attributed the increased rate to a peptide-induced membrane pore, whereas Anglin et al 49 suggest instead that melittin facilitates Figure 2A shows that this (small) pore first appears when the lipid head is constrained to lie 0.4 nm away from the bilayer centre. Figure 2B shows a sequence of snapshots from the sampled umbrella window at this lipid distance.…”
Section: Melittin Facilitates Membrane Defect Formation Through Lipidmentioning
confidence: 97%
“…It is worth noting in this context, that a number of experimental studies have concluded that antimicrobial peptide adsorption can induce more rapid lipid flip-flop rates in the bilayers. Fattal et al 47 and Matsuzaki et al 48 attributed the increased rate to a peptide-induced membrane pore, whereas Anglin et al 49 suggest instead that melittin facilitates Figure 2A shows that this (small) pore first appears when the lipid head is constrained to lie 0.4 nm away from the bilayer centre. Figure 2B shows a sequence of snapshots from the sampled umbrella window at this lipid distance.…”
Section: Melittin Facilitates Membrane Defect Formation Through Lipidmentioning
confidence: 97%
“…We note that melittin has also been reported to enhance lipid flip-flop rates [98]. However, a thermodynamic study by Anglin et al indicates that melittin facilitates lipid flip-flop by thinning the lipid bilayer, rather than by generating membrane pores [98].…”
Section: Magaininmentioning
confidence: 70%
“…A large fraction of the lipids in the upper monolayer were clearly displaced by the dendrimer and transferred to the proximal leaflet until full surface coverage was reached (100%). Flip-flop of lipids in a gel-phase membrane is typically extremely slow with a half-life of several hours, but it is speeded up by defects [49] as well as by membrane-penetrating molecules such as peptides [50,51]. Therefore, it is not surprising that flip-flop of gel-phase DPPC was observed in the incomplete supported bilayer upon dendrimer penetration.…”
Section: Baly Inserts Into the Outer Leaflet Of Fluid Membranesmentioning
confidence: 99%